2022
DOI: 10.3389/fpubh.2022.932017
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional associations between screen time and the selected lifestyle behaviors in adolescents

Abstract: BackgroundIn adolescents, excessive screen time leads to many adverse health outcomes and is associated with a variety of lifestyle behaviors. This study was conducted to investigate the associations between the two types of screen time and a variety of lifestyle behaviors in American adolescents.MethodsBased on the Youth Risk Behavior Surveillance System, this cross-sectional study was conducted. With the help of data collectors, participants self-reported screening time, lifestyle behaviors, and demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 56 publications
0
0
1
Order By: Relevance
“…This is probably due to students taking these fruits as snacks having been preoccupied with video games, which hinders their urge to prepare meals or look for already prepared meals at the time. This result contradicts Fan et al [51] who stated that the more adolescents played video games, the less fruits they consumed. The nding, likewise, implies that the more a student does house chores the more they eat fruits.…”
Section: Discussioncontrasting
confidence: 60%
“…This is probably due to students taking these fruits as snacks having been preoccupied with video games, which hinders their urge to prepare meals or look for already prepared meals at the time. This result contradicts Fan et al [51] who stated that the more adolescents played video games, the less fruits they consumed. The nding, likewise, implies that the more a student does house chores the more they eat fruits.…”
Section: Discussioncontrasting
confidence: 60%
“…La literatura también indica asociación de la inactividad física con los niveles socioeconómicos 20 , en nuestro caso los estratos bajos tienen menos probabilidad de inactividad (ORa=0,59; IC 95% 0,44 -0,79). Otros estudios mostraron que las actividades sedentarias como observar televisión por más de dos horas diarias incrementaba los riesgos de consumo de alcohol, fumar y presentar inactividad física 21 . Este estudio encontró que el consumo de licor (ORa=2,62; IC 95% 1,77 -3,87) y cafeína (ORa=1,59; IC 95% 1,19 -2,12) aumenta el riesgo de inactividad física.…”
Section: Discussionunclassified
“…This association was also supported when the quality of life score was assessed in adolescents, with quality showing negative associations with higher screen time and positive with higher physical activity 27 . Increased screen time (and television screen time in particular) was positively associated with higher risk of smoking in a cross-sectional study which was conducted in adolescent, when television screen was >2 hours/day 28 . In addition to the above, a study that was also conducted in adolescents, found that smoking was positively associated with problematic use of internet and as a possible predictor for internet addiction 29 .…”
Section: Screen Time For Work (First Row) or Entertainment (Second Ro...mentioning
confidence: 98%